Socio-cognitive processes in mild-moderate depression - Raghavendra, Prathima Alevoor; Hegde, Shantala; Philip, Mariyamma; Muralidharan, K. (Frontiers in Psychology, 2025)
BackgroundSocial cognition (SC), the ability to interpret and respond to social situations appropriately, is essential for effective interpersonal functioning. Challenges in these areas are a core feature of depression. Evidence shows mixed findings regarding the extent and presence of these deficits in depression, especially in its milder forms. SC comprises key processes such as the theory of mind (ToM), attribution style, emotion, and social perception. In addition to exploring emotion perception (EP) ability through faces and vocal stimuli, music has recently emerged as a valuable tool in studying EP, given the effectiveness of music intervention in improving mood and overall emotional functioning in patients with depression.AimThis study aimed to explore social cognition abilities in patients with mild–moderate major depressive disorder (MDD) and investigate the relationship between SC and neurocognition in depression.MethodsNineteen patients diagnosed with mild–moderate MDD and eighteen age-, sex-, and education-matched healthy controls (HCs) (n = 18) were assessed using the Social Cognition Rating tools in the Indian Setting (SOCRATIS), the NIMHANS Emotion Perception Test (NEPT; assessing facial and prosodic domains), and the Music Emotion Perception Test (MEPT).ResultsPatients with MDD showed significant deficits in first-order ToM (FOT) compared to HCs (p = 0.01). On the music emotion recognition test, the MDD group rated the intensity of positive emotions (e.g., happiness) significantly lower than the HC group (p = 0.007). However, no significant group differences were found in the accuracy of emotion identification across facial, prosodic, or musical stimuli. Correlational analyses revealed trends toward significant positive associations between attention and second-order ToM (SOT; r = 0.58, p < 0.01), as well as between the executive function (EF) index and EP (r = 0.60, p < 0.01), SOT (r = 0.56, p = 0.01), and social perception (r = 0.60, p < 0.01).ConclusionIndividuals with mild–moderate depression show reduced FOT ability and emotion scaling of positive emotions on music excerpts. A potential association exists between neurocognitive (attention and EFs) and SC measures.